Pelatihan Pembuatan Media Pembelajaran Berbasis Karakter Religius Menggunakan Canva Di SDN Tanon 2 - Santy Andrianie; Lailatul Arofah; Rosalia Dewi Nawantara; Ariyanto, Restu Dwi (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2021)
Religious character is an important thing that must be instilled in students in current developments, especially in elementary school (SD) settings. Efforts to develop learning media related to religious characters have been carried out, one of which is based on information technology. Learning media innovations that are developed must pay attention to creative content packaging so that students can easily understand the material presented. Implementation in the field shows that the mastery of information technology in SDN Tanon 2 teachers is not optimal. The teacher has a strong motivation to learn to make learning media but there is no accompanying facilitator. Of course, this will affect the media content and the process of delivering maximum material to students. From this problem, a scheduled training forum for elementary school teachers is needed to develop good and interesting learning media. The method of service activities is carried out by carrying out webinar series activities, training in making learning media, and evaluation. The results of the service activities show that the trainees can improve competence in developing learning materials with the Canva application.